Successful Anesthetic Management in Cesarean Section for Pregnant Woman with COVID-19 - Bani Hani, Diab A. (Am J Case Rep, 2020)
Patient: Female, 29-year-old Final Diagnosis: COVID-19 Symptoms: Pregnancy Medication: — Clinical Procedure: Cesarian section • spinal anesthesia Specialty: Anesthesiology OBJECTIVE: Unusual setting of medical care BACKGROUND: The current COVID-19 pandemic highlights the importance of the mindful use of financial and human resources. Preventing infections and preserving resources and manpower are crucial in healthcare. It is important to ensure the ability of surgeons and specialized interventionalists to function through the pandemic. Until now, no justified protocol has been reported for the anesthetic management in cesarean section (CS). CASE REPORT: A 29-year-old pregnant woman, G2P1 at 37+4 weeks of gestation, was referred to our center on March 28, 2020, after she had tested positive for COVID-19. She was stable and the CS was planned after she reached term. Through spinal anesthesia, CS was conducted. The anesthesia team was protected with full personal protection equipment. The operation was carried out smoothly without complication. A female neonate was delivered and was tested to be negative for COVID-19. No medical staff cross-infection was reported. CONCLUSIONS: Special precautions should be considered when pregnant women are undergoing CS. Spinal anesthesia is preferred over general anesthesia.